Pengaruh Penguasaan Teknologi Informasi Terhadap Kinerja Karyawan Pada PT. Telkom Indonesia Cabang Manado - Handayani, Ratina; Runtuwene, Roy F.; Sambul, Sofia A. P. (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
This research is background be based on phenomenon where the factor of information technology mastery can influential to performance employee at PT. Telkom Indonesia Branch Manado. The purpose of this research is to know about the effect of information technology mastery to performance employee in PT. Telkom Indonesia Branch Manado. The method research is research of descriptive quantitative with sample as much as 65 respondent that is obtained using saturated sampling method. At this research the independent variable is information technology mastery, and dependent variable is performance employee. The experiment instrument use validity test and reliability test, but analysis data method use analysis simple linier regression method with t test, and coeficcient determinant. Result of research t tes analysis, where independent variable (information technology mastery) gained tvalue (10,873) bigger than  ttable (1,999)  influential significance to performance employee and significance 0,000 < 0,05  so, H0 rejected and Ha accepted that mean independent variable (information technology mastery) influential to dependen variable (performance employee) with positive and significance. The result of coeficcent determinant analysis  showed that the  rate R Square is 0.652 or 65,2%, that means is performance employee variable can be explain by information technology mastery, while the rest 34,8% can be explain by other variable outside the  research variable. This research expect a company can always conduct an evaluation regularly to information technology mastery of  each employee on performance result that have been achieved and evaluation of innovation for the progress of company that will come.